Land Markets and its Effects on the Spatial Segregation: The Case of Ciudad Juarez, Mexico - César M. Fuentes; Luis E. Cervera (Estudios Fronterizos, 2006)
The objective of this article is to analyze the land market imperfec-tions and their effect on spatial segregation. It uses a spatial approach through the construction of socio-spatial segregation and infrastructure deficit indexes. The principal component element was used to estimate the socio-spatial in-dexes at the AGEB scale. The data used to calculate the indexes was obtained from the XII Population and Housing Census at census tracts level. The result show that the city suffers from spatial segregation caused mainly by land market imperfections. The land market is not able to ensure an adequate supply at affordable prices and as a result, the biggest sufferers have been the urban poor. The lack of access to urban land has pushed low income inhabitants to the outer limits of the urban core: low value areas without public infrastructure.